Modulatory upregulation of an insulin peptide gene by different pathogens in C. elegans. Issue 1 (1st January 2018) - Lee, Song-Hua; Omi, Shizue; Thakur, Nishant; Taffoni, Clara; Belougne, Jérôme; Engelmann, Ilka; Ewbank, Jonathan J.; Pujol, Nathalie
ABSTRACT: When an animal is infected, its innate immune response needs to be tightly regulated across tissues and coordinated with other aspects of organismal physiology. Previous studies with Caenorhabditis elegans have demonstrated that insulin-like peptide genes are differentially expressed in response to different pathogens. They represent prime candidates for conveying signals between tissues upon infection. Here, we focused on one such gene, ins-11 and its potential role in mediating cross-tissue regulation of innate immune genes. While diverse bacterial intestinal infections can trigger the up-regulation of ins-11 in the intestine, we show that epidermal infection with the fungus Drechmeria coniospora triggers an upregulation of ins-11 in the epidermis. Using the Shigella virulence factor OpsF, a MAP kinase inhibitor, we found that in both cases, ins-11 expression is controlled cell autonomously by p38 MAPK, but via distinct transcription factors, STA-2/STAT in the epidermis and HLH-30/TFEB in the intestine. We established that ins-11, and the insulin signaling pathway more generally, are not involved in the regulation of antimicrobial peptide gene expression in the epidermis. The up-regulation of ins-11 in the epidermis does, however, affect intestinal gene expression in a complex manner, and has a deleterious effect on longevity. These results support a model in which insulin signaling, via ins-11, contributes to the coordination of the organismal response to infection, influencing the allocation of resources in an infected animal.